Contrast enema for Hirschsprung disease investigation: diagnostic accuracy and validity for subsequent diagnostic and surgical planning - Frongia, Giovanni; Günther, Patrick; Schenk, Jens-Peter; Strube, Kai; Kessler, Markus; Mehrabi, Arianeb; Romero, Philipp (European journal of pediatric surgery, 2016)
Introduction A targeted Hirschsprung disease (HD) diagnostic is necessary, as it determines a specific approach primarily based on surgical resection of the affected aganglionic colonic segment. The aim of this study was to evaluate the diagnostic accuracy of a contrast enema (CE) for HD diagnosis and to determine whether it should be performed before or after rectal biopsies (RBs). Methods A retrospective observational study of children undergoing RB for HD investigation was performed. In the performed CE, the occurrence and the level of a colonic caliber change (CCC) were recorded and its concordance with the histologically assessed level of aganglionosis by RB and the odds ratio were calculated. Results A total of 107 cases were included. Sensitivity and specificity for a CCC in CE were 74.1% and 94.6%. A CCC present in CE was associated with a 50-fold increased probability for a histologically proven HD. The overall concordance between a CCC and the histologically assessed level of aganglionosis was high (kappa 0.642, p = 0.003), being correct in 94.4% of cases when the CCC was located in the rectosigmoid, but only in 50% of cases when it was located in more proximal segments. By performing a CE only after HD diagnosis confirmation by RB would avoid 67.5% of CE with no loss of diagnostic accuracy. Conclusion We confirm that CE is a valuable tool for HD diagnosis; however, it should only be performed for subsequent diagnostic and surgical planning following histological confirmation of HD by RB. On the basis of this, an algorithm for an optimized investigation and management of HD is presented.
published online March 24, 2015
Gesehen am 07.02.2020